Mapping resistant QTLs for rice sheath blight disease with a doubled haploid population - Yu-xiang ZENG; Ling-zhi XIA; Zhi-hua WEN; Zhi-juan JI; Da-li ZENG; Qian QIAN; Chang-deng YANG (Journal of Integrative Agriculture, 2015)
Sheath blight (SB) disease, caused by Rhizoctonia solani Kühn, is one of the most serious diseases causing rice (Oryza sativa L.) yield loss worldwide. A doubled haploid (DH) population was constructed from a cross between a japonica variety CJ06 and an indica variety TN1, and to analyze the quantitative trait loci (QTLs) for SB resistance under three different environments (environments 1–3). Two traits were recorded to evaluate the SB resistance, namely lesion height (LH) and disease rating (DR). Based on field evaluation of SB resistance and a genetic map constructed with 214 markers, a total of eight QTLs were identified for LH and eight QTLs for DR under three environments, respectively. The QTLs for LH were anchored on chromosomes 1, 3, 4, 5, 6, and 8, and explained 4.35–17.53% of the phenotypic variation. The SB resistance allele of qHNLH4 from TN1 decreased LH by 3.08 cm, and contributed to 17.53% of the variation at environment 1. The QTL for LH (qHZaLH8) detected on chromosome 8 in environment 2 explained 16.71% of the variation, and the resistance allele from CJ06 reduced LH by 4.4 cm. Eight QTLs for DR were identified on chromosomes 1, 5, 6, 8, 9, 11, and 12 under three conditions with the explained variation from 2.0 to 11.27%. The QTL for DR (qHZaDR8), which explained variation of 11.27%, was located in the same interval as that of qHZaLH8, both QTLs were detected in environment 2. A total of six pairs of digenic epistatic loci for DR were detected in three conditions, but no epistatic locus was observed for LH. In addition, we detected 12 QTLs for plant height (PH) in three environments. None of the PH-QTLs were co-located with the SB-QTLs. The results facilitate our understanding of the genetic basis for SB resistance in rice.